An Analysis of Word Formation Processes Used by Food Vloggers - Elsa Octavia; M. Zaim (Universitas Negeri Padang, 2022)
Word formation process is the tool to form a new word based on several techniques that involve the word itself. The aim of this research is to analyze and to find out the types and the most dominant types of word formation process of words related to food used by food vloggers. The data of this research were utterances from the food vloggers namely Luke Martin, Trevor James, Mark Wiens, Mina Oh, Mike Chen, and Sonny Side in their vlogs on YouTube. The data were analyzed based on several word formation process theories. This research used descriptive method. Based on the data analysis, the researcher found 196 words containing the word formation process related to food and 7 out of 11 types of word formation process. They are (1) borrowing, (2) compounding, (3) clipping, (4) conversion, (5) derivation, (6) inflection, and (7) multiple process. The finding shows that this research is dominated with borrowing process with the frequency of 60 data (31%).